“Dealer raus”: A retrospective case study of the Mothers Without Borders Initiative in Berlin’s Kreuzberg - Ağca Varoğlu, Fatma Güzin (Addicta: The Turkish Journal on Addictions, 2026)
This article presents a retrospective case study of community-based responses to substance use and street-level distribution in Kottbusser Tor, known as “Little Istanbul,” a neighborhood in Berlin’s Kreuzberg with a high concentration of immigrants from Türkiye and their descendants. The study examines the Mothers Without Borders (Mütter ohne Grenzen) initiative, active in the early 2000s under the leadership of second-generation immigrant Turkish women. It is based on a document analysis of media coverage from 2005 to 2013, including news reports, interviews, blog posts, social media content, and institutional brochures. These are examined thematically to explore how the experience of Mothers Without Borders can be interpreted in the context of media representations and these women’s statements. Conceptually, the study engages with debates concerning migration, motherhood, and neighborhood space, and draws notably on perspectives that understand addiction as embedded within broader socio-spatial and political processes rather than just as an individual or purely medical issue. The findings show that the women, as long-term Kreuzberg residents, mobilized to disrupt the emerging cycle of substance use and street-level distribution among younger generations. Instead of seeing the neighborhood solely as a site of anti-drug activism, they reconceptualized it as a space where belonging and intergenerational care could be rearticulated. Their experience indicates that efforts to address the conditions fostering substance use and distribution can also be viewed as resistance to the stigmatization of immigrant neighborhoods. In this context, the women’s positionality is constructed through “dual positioning,” in which motherhood is strategically mobilized as both a tool for activism and for neighborhood protection. By emphasizing grassroots mobilization, the article contributes to migration, space, and addiction studies by foregrounding immigrant women’s agency against addiction as relationally constituted within intersecting power relations and socio-spatial inequalities.